Factors Affecting The Incidence of Dengue Hemorrhagic Fever (DHF ) At Tumpaan Health Center, South Minahasa Regency - Revony Yulli Turang; Grace D. Kandou; Eva M. Mantjoro (International Journal of Health and Pharmaceutical (IJHP), 2025)
This study presents a comprehensive analysis of the factors influencing Dengue Hemorrhagic Fever (DHF) incidence in the working area of Puskesmas Tumpaan, South Minahasa. Utilizing a case-control design, 88 respondents—44 laboratory-confirmed DHF cases and 44 matched controls—were assessed to determine the association between behavioral and environmental risk factors and DHF transmission. Five key variables were examined: level of public knowledge, vector control practices (PSN), indoor clothing habits, household cleanliness, and water storage conditions. Bivariate and multivariate statistical analyses were employed to evaluate significant predictors of disease occurrence. The results identified knowledge about DHF (OR = 0.27; p = 0.013) and the habit of hanging clothes indoors (OR = 0.15; p = 0.000) as significant risk factors. Other variables—PSN, household cleanliness, and water storage—showed no statistical significance but remain epidemiologically relevant. These findings indicate that behavioral factors, particularly knowledge and indoor clothing practices, play a central role in influencing dengue transmission in endemic regions. The study underscores the importance of integrated health education and behavior-focused interventions in dengue prevention strategies.